DEVELOPMENT STRATEGY OF E-POCKET BOOK TO OPTIMIZE ALGEBRAIC THINKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Artasari, Adika; Oktaviyanthi, Rina (Universitas Labuhanbatu, 2024)
Many middle school students face challenges in developing algebraic thinking skills, which hinders their understanding and application of algebraic concepts. This study aims to develop an E-Pocket Book as a learning medium to optimize middle school students’ algebraic thinking skills. The research employs a development method using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of this study are eighth-grade students from SMPN 14 in Serang City. The research instruments include both tests (cognitive tests) and non-tests (questionnaires). The cognitive test was administered to 59 students during the field trial and 8 students during the limited trial, with the results showing significant improvement in students’ algebraic thinking skills, with increases of 71% and 79%, respectively. The non-test instruments consist of two types of questionnaires: assessment questionnaires and response questionnaires. The assessment questionnaire was given to two subject matter experts, who rated the e-pocket book as feasible (85.2%), and one media expert, who rated it highly feasible (93%). The response questionnaire was distributed to both mathematics teachers and students, with an overall feasibility rating of 80% from teachers and 87% from students. The findings indicate that the e-pocket book is a viable learning medium and effectively enhances students’ algebraic thinking abilities.